Transport policy and planning : an integrated analytical approach - Bayliss, Brian (World Bank WashingtonUS, 1992)
Demonstrates how a transport model can be used to evaluate policies, to compare it with other kinds of models, and to examine the use of models in the wider context of policy objectives and instruments.